The meaning of negation in the second language classroom: Evidence from 'any'. (March 2019) - Gil, Kook-Hee; Marsden, Heather; Whong, Melinda
This article brings together an experimental study involving L2 knowledge of negation in English and an analysis of how English language textbooks treat negation, in order to consider whether textbook explanations of negation could better exploit linguistic insights into negation. We focus on the English negative polarity item any, whose distribution is contingent on negation, whether through the explicit negator not or through lexical semantic negators (e.g. hardly ). Our experiment compares Chinese-speaking learners with existing data from Arabic-speaking learners, finding lower accuracy on any with lexical semantic negators in both groups. Our textbook analysis reveals an approach to negation that is limited to form, focusing on the explicit negator not without explicit treatment of other types of negation. We propose that emphasizing the meaning of negation, with explicit treatment of the full range of negative forms could facilitate more complete acquisition across a range of grammatical properties where negation plays a role.